Grammatophyllum speciosum Ethanolic Extract Promotes Wound Healing in Human Primary Fibroblast Cells - Saraporn Harikarnpakdee; Verisa Chowjarean (International Journal of Cell Biology)
Grammatophyllum speciosum is a plant in Orchidaceae family which contains a variety of phytochemical compounds that might be beneficial for medicinal use. This study aimed to evaluate the activity of pseudobulb of G. speciosum extract (GSE) in wound healing processes in human primary fibroblast cells along with in vitro antioxidant activity and total phenolic content of GSE. Scratch wound healing assay indicated that GSE was capable of increasing migration rate after 6 and 9 hours of treatment. Besides, the extract was able to scavenge DPPH, ABTS, and superoxide anion radicals indicating the antioxidative property of GSE. This study suggested a novel role of the of pseudobulb extract of G. speciosum as a wound healing enhancer. The results from this study might be beneficial for the development of further novel active compounds for skin wound healing.